Analisis Semantik Perumpamaan Acara Adat Perkawinan Suku Simalungun - Besti Desmaria Purba; Charles Butar-Butar (Medan Resource Center, 2023)
This study aims to find out the meaning of the parable of the Isimalungun marriage custom. iThis research uses qualitative descriptive method. i Descriptive research is generally carried out with the main objective, i.e., to describe systematically the facts and characteristics of the object or subject that is being studied accurately. The technique used is a type of qualitative technique. The analysis of data in this research focuses on the meaning of the parables found in the ceremony of the customary marriage ceremony, iSimalungun. To see if there is or not the meaning of the idiom in the parable of the speaker, the writer also reads the data written in i, namely my mother, the book which contains the conversation in the iSimalungun language. Then the writer finds the data and writes it in the list, followed by determining the direct or indirect example. The results of the study can be concluded that there is a parable in the traditional wedding ceremony of the Simalungun tribe.